Geographic Information System Of Fishing Spot Tourism Search In Sidoarjo Website Based - Muhammad Fedy Rifki; Yulian Findawati (Universitas Muhammadiyah Sidoarjo, 2021)
In 2020 fishing hobby is increasingly popular with young people, especially in the Sidoarjo area. In addition to wanting to feel the sensation of fishing, in some fishing tourism locations there are usually many additional facilities to attract the place such as coffee shop facilities, lesehan, toys for children and so on which are used as time to gather with families and organizations. The Fishing Tourism Location Information System that is currently running in the Sidoarjo area is still using the method of word of mouth, so it will take a lot of time so that the location can be known by various people, especially the newly established fishing tourism location. The results of this study are to help fishing tourism owners promote their tours so that they are easy to find, and to help anglers make it easier to find fishing spots that suit their desires.